Pengaruh Model Pembelajaran Somatic, Auditory, Visual, Intelectual Terhadap Kemampuan Pemahaman Konsep Matematis Siswa Berbantuan JACAMA - Irawan, Syakia Kirti; Hendriana, Evinna Cinda; Kariadi, Dodik (MES: Journal of Mathematics Education and Science, 2024)
This study aims to determine whether there is an effect of the Somatic Auditory Visual Intelectual (SAVI) learning model on students' mathematical concept understanding skills assisted by JACAMA. The type of research used is quantitative research with quasy experimental design method, post-test only control group design. The samples taken in this research were VB class students totaling 23 students of SD Negeri 12 Singkawang. The data collection technique used questionnaires and essay-shaped tests containing indicators of students' understanding of mathematical concepts. Data analysis technique using t test and percentage of student response questionnaire. The research results obtained are: 1) Students' responses to learning media taught with SAVI learning models in grade V elementary school have good criteria; 2) The SAVI learning model assisted by JACAMA has a major effect on students' mathematical concept understanding ability as shown by Es, namely 1.30 with high criteria; 3) There is a difference in students' mathematical concept understanding ability between those taught with the SAVI learning model assisted by JACAMA and those who apply the direct learning model in class V SD Negeri 12 Singkawang.